Assessment of Protective Clothing Used by Chemical Industry Workers in Pakistan : Chemical Resistance of Protective Clothing - Ijaz, M.; Sahar, N. E.; Tariq, Z.; Fatima, R.; Rasheed, Z.; Tariq, M.; Munir Dar, H. (Engineering, Technology & Applied Science Research, 2022)
Protective clothing serves as a barrier against many hazards faced by workers in the industry. This study aimed to investigate the performance of locally manufactured clothing used by workers in the chemical industries in Pakistan. The construction parameters were determined using international test procedures for all samples. Then, these were assessed for their chemical resistance behavior after various laundering intervals, following the ISO 6530:2005 test method. After the investigation, it was observed that the collected samples failed to meet the minimum criteria for penetration and repellency through their structure. The samples were unable to repel a minimum of 95% liquid chemical and penetrated it more than 5%, even at zero wash. These conditions worsened with each washing interval. Clothing materials should always be checked for their performance before use to protect workers at workplace.